Estimating the Relevant Source Area of Pollen in the past cultural landscapes of southern Sweden — A forward modelling approach - Hellman, Sofie; Gaillard, Marie-José; Bunting, Jane Mairi; Mazier, Florence (Review of palaeobotany and palynology, 2009)
In this paper, we estimate the Relevant Source Area of Pollen (RSAP) in past hypothetical landscapes of the Middle and Late Holocene in southern Sweden, in order to explore the possible effects of past changes in vegetation composition, openness and structure in terms of patch size and spatial distribution. The RSAP of small basins (bogs or lakes) in the past has to be estimated if quantitative reconstruction of past vegetation at the local spatial scale is to be achieved using Sugita's Landscape Reconstruction Algorithm (LRA). In this study we apply a forward modelling approach to estimate past RSAP using the computer simulation model HUMPOL. The landscape designs are based on past landscape maps produced using a combination of palaeobotanical, archaeological and historical data, and the area's geology and soil characteristics. Four time windows characterised by different landscape/land-use were selected, i.e. Early Neolithic, Late Bronze Age, Viking Age, and Middle Ages. We found that RSAP estimates for hypothetical past landscapes in Skåne differ by ca. 600 m to 1200 m between the selected time periods, whatever the size of the basin (lake or bog, 25–250 m radius). The most probable explanation for the differences in RSAP between time slices is variable patch size and spatial distribution of patches in the landscape. The RSAPs vary between ca. 1200 and 2300 m for small basins (25 m and 70 m radius), and between ca. 2000 and 3000 m for larger basins (250 m radius). These values are within the range of earlier estimates of modern and past RSAPs for southern Scandinavia obtained using simulated or empirical data. These results suggest that, given the type of setting of that region in terms of taxa composition and traditional land-use, the RSAP for small-size lakes (25–250 m radius) will generally be in the range ca. 1200–3000 m. The forward modelling approach is found to be useful to assess the possible effects on RSAP of changes in vegetation/landscape characteristics between different periods of the past. Moreover, comparison of RSAP estimates obtained using both the forward and backward modelling approaches will be important to identify the most credible RSAP estimates for the past.